Identification of the production system of beef cattle by the stable isotope analysis - Perdigao, Alexandre [UNESP]; Martins, Cyntia Ludovico [UNESP]; Vieira Junior, Luiz Carlos [UNESP]; Pereira Sartori, Maria Marcia [UNESP]; Niehues, Maria Betania [UNESP]; Arrigoni, Mario De Beni [UNESP] (Empresa Brasil Pesq Agropec, 2020)
The objective of this work was to evaluate the potential of the stable isotope technique to characterize beef cattle production systems in tropical conditions. For this, carbon and nitrogen stable isotopes were identified in non-defatted and defatted bovine muscles. A total of 45 cattle were evaluated in three production systems: pasture, conventional feedlot, and young beef bull feedlot (n = 15 per system). Samples from the Trapezius cervicis, Longissimus dorsi, and Semitendinosus muscles were collected to determine the isotopic composition of delta C-13 and delta N-15. The isotopic data of the delta C-13 and delta N-15 of non-defatted and defatted muscles were subjected to the principal component analysis (PCA) and to the discriminant analysis (DA). The PCA allowed separating the three production systems based on the results obtained for the non-defatted and defatted muscles. A correct global classification rate of 100% and a cross-validation rate of 100% were obtained with the DA. The carbon and nitrogen isotopic ratio of non-defatted and defatted muscles allows for the precise identification of beef cattle production systems in tropical conditions.
Keywords: muscle tissue; Nelore; production system; traceability